Aerodynamics of vortex ingestion for aero-engines - McLelland, Grant (Cranfield University, 2013)
The potential impact of inlet flow distortion on the stability and performance of aircraft engines remains a key concern for engine-airframe integration. Current and future configurations, such as Unmanned Combat Air Vehicles (UCAVs), and possible civil aircraft with large rear-mounted engines, feature closely-coupled intake and airframe aerodynamics. Such configurations are susceptible to the ingestion of streamwise vorticity generated upstream on the aircraft. There is a dearth of understanding of this ingestion process which, crucially, determines the nature of the flow distortion presented to the turbomachinery. To assess the risk of engine stability and performance deterioration, it is therefore necessary to understand and model the vortex ingestion process. This research provides a novel application of Stereoscopic Particle Image Velocimetry (Stereo PIV) to obtain quantitative measurements of a streamwise vortex inside a contracting intake capture streamtube. The experiments were conducted in the 8’x6’ lowspeed wind tunnel using a 1/30th scale intake model. Vortex generators were employed to create a streamwise vortex in the flow upstream of the intake. The streamtube contraction levels, vortex generator type, and vortex generator configuration were varied to establish fundamental understanding on the flow physics of vortex ingestion. The vortex experiences notable levels of intensification as it passes through the contracting streamtube. The evolution of the vortex is strongly dependent on the streamtube contraction levels, the initial characteristics of the vortex prior to ingestion, and the trajectory that the vortex follows inside the capture streamtube. In addition, detailed studies have been performed using Computational Fluid Dynamics (CFD) to establish an approach to simulate vortex ingestion flows. A number of guidelines have been developed using experimental measurements to ensure that the flow physics of vortex ingestion are captured. This approach permits vortex ingestion simulations to be performed to evaluate the inlet flow distortion characteristics in full-scale intake flows.